Human capital and degree of internationalization. An empirical study on Costa Rican companies - Sandoval Álvarez, Carlos Alberto (2024)
This study examines the influence of managers’ international orientation, international experience, and export risk perception on the degree of internationalization achieved by their small and medium-sized companies. Based on the existing literature and previous research into International Entrepreneurship, a research model was developed and empirically tested using structural equation modeling techniques on a sample of 132 managers of small and medium-sized companies. The main results indicate that the international experience of managers has only an indirect effect on the degree of internationalization. Managers’ risk perception regarding exports seems to be a key factor to explain the variation in the degree of internationalization of small and medium-sized companies.